Immunotherapy in endometrial cancer. Issue 3 (6th March 2023) - Mahdi, Haider; Chelariu-Raicu, Anca; Slomovitz, Brian M
Abstract : The Cancer Genome Atlas (TCGA) endometrial cancer data expanded our knowledge about the role of different immunotherapeutic approaches based on molecular subtypes. Immune checkpoint inhibitors demonstrated distinct antitumor activities as monotherapy or in combination. In microsatellite unstable (microsatellite instability-high) endometrial cancer, immunotherapy with immune checkpoint inhibitors showed promising single agent activity in recurrent settings. Different strategies are needed to enhance the response or reverse resistance to immune checkpoint inhibitors, or both, in microsatellite instability-high endometrial cancer. On the other hand, single immune checkpoint inhibitors showed underwhelming efficacy in microsatellite stable endometrial cancer but this was significantly improved using a combination approach. Furthermore, studies are also needed to improve response along with ensuring safety and tolerability in microsatellite stable endometrial cancer. This review summarizes the current indications of immunotherapy for the treatment of advanced and recurrent endometrial cancer. We also outline potential future strategies for an immunotherapy based combination approach in endometrial cancer to combat resistance or enhance response to immune checkpoint inhibitors, or both.